CT image quality over time: comparison of image quality for six different CT scanners over a six‐year period - Roa, Ana Maria A. (J Appl Clin Med Phys, 2015)
UNSCEAR concluded that increased use of CT scanning caused dramatic changes in population dose. Therefore, international radiation protection authorities demand: 1) periodical quality assurance tests with respect to image quality and radiation dose, and 2) optimization of all examination protocols with respect to image quality and radiation dose. This study aimed to evaluate and analyze multiple image quality parameters and variability measured throughout time for six different CT scanners from four different vendors, in order to evaluate the current methodology for QA controls of CT systems. The results from this study indicate that there is minor drifting in the image noise and uniformity and in the spatial resolution over time for CT scanners, independent of vendors. The HU for different object densities vary between different CT scanner models from different vendors, and over time for one specific CT scanner. Future tests of interphantom and intraphantom variations, along with inclusion of more CT scanners, are necessary to establish robust baselines and recommendations of methodology for QA controls of CT systems, independent of model and vendor. PACS number: 07, 87